2009
DOI: 10.1002/aic.11732
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the phase behavior of ternary systems ionic liquid + organic + CO2 with a Group Contribution Equation of State

Abstract: in Wiley InterScience (www.interscience.wiley.com).This work presents the results of the use of a Group Contribution Equation of State (GC-EOS) to model experimental data obtained for ternary systems of the type bmim[BF 4 ] þ organic solute þ CO 2 with four different organic compounds, namely acetophenone, 1-phenylethanol, 4-isobutylacetophenone, and 1-(4-isobutylphenyl)-ethanol. Our results show that the GC-EOS is able to qualitatively predict not only LþV!L but also L 1 þL 2 !L phase transitions. As the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…They obtained AAD values between 0.9 and 3%, showing a good agreement between predicted and experimental values. Kuhne [100]. This time, they obtained AAD values between 5 and 21% and the authors claim that the model presents acceptable agreement between calculated and experimental values.…”
Section: Group Contribution Eosmentioning
confidence: 80%
See 1 more Smart Citation
“…They obtained AAD values between 0.9 and 3%, showing a good agreement between predicted and experimental values. Kuhne [100]. This time, they obtained AAD values between 5 and 21% and the authors claim that the model presents acceptable agreement between calculated and experimental values.…”
Section: Group Contribution Eosmentioning
confidence: 80%
“…Martín et al also applied a group contribution EoS (the same as the one used in references [99] and [100]) to calculate the phase behaviour of gases CO 2 , O 2 and SO 2 in ionic liquids with the NTf 2 anion and cations of the families 2,3-dimethylimidazolium, 1-alkyl-1-methylpyrrolidinium and 1-alkyl-3-methylpyridinium [102], and to describe the phase behaviour of gases H 2 , CO, C 2 H 4 , O 2 , SO 2 , CH 3 OH, N 2 O and Xe in ionic liquids of the family [C n mim][NTf 2 ] [103]. They used the same methodology mentioned before [99] to decompose the ionic liquids.…”
Section: Group Contribution Eosmentioning
confidence: 98%
“…Very recently, Kuhne et al [147] have used the same approach and extended it to the calculation of ternary mixtures of [C 4 mim][BF 4 ] + organic solute + CO 2 , being able to qualitatively predict liquid-vapor and liquid-liquid phase transitions.…”
Section: Group Contribution Eosmentioning
confidence: 94%
“…In this work, Breure et al [19] showed that the relatively simple GC-EoS could describe the high pressure phase behavior (CO 2 + IL) systems, and that by application of the group contribution concept it is possible to predict the phase behavior of a complete family of ILs by application of a parameter set obtained by fitting experimental data corresponding to a few members of the family. This EoS has also been used to describe the phase behavior of ILs of the 1-alkyl-3-methylimidazolium bis[(trifluoromethyl)sulfonyl]imide family in combination with CO 2 , H 2 , and CH 4 [20], ionic liquids of the 3-methyl imidazolium nitrate ([-mim][NO 3 ]) family with CO 2 [21] and the phase behavior of ternary mixtures of the ionic liquid [bmim][BF 4 ] with CO 2 and different organic solvents such as acetophenone, 1-phenylethanol, 4-isobutylacetophenone, and 1-(4-isobutylphenyl)-ethanol [22].…”
Section: Introductionmentioning
confidence: 99%
“…If the parameters of the characteristic functional group of a IL family are fitted by using data of a reduced number of ILs of the family, then the phase behavior of all the ILs of the same family can be predicted using exclusively the data of the pure components. Previously, the parameters of the IL families with an imidazolium-based cation and the anions PF 6 , BF 4 NO 3 , and Tf 2 N were fitted to experimental data [19], and some ternary systems (CO 2 + organics + ionic liquid [bmim][BF 4 ]) were also modeled [22]. In this work, the GC-EoS was used to calculate phase behavior of gases {(CO 2 , O 2 , or SO 2 ) + ionic liquids} with Tf 2 N anion and cations of the families 2,3-dimethyl-imidazolium, 1-alkyl-1-methyl-pyrrolidinium, and 1-alkyl-3-methyl-pyridinium.…”
mentioning
confidence: 99%